A Review on Prospective Energy Models: The Moroccan Case - Defaf, Mohamed; Tkiouat, Mohamed (International Journal of Energy Economics and Policy, 2021)
Nowadays, energy modeling is among the most required tools for the optimization of the energy system performance on a regional, national and global scale. The need for studies of energy models is justified by the increasing energetic demand, the evolution of power generation technologies and the transition to modern economics for developing countries. The aim of this study is to provide different aspects, techniques and characteristics of the existing energy models in literature. A better understanding of each model framework and requirements may lead to a better analysis of the Moroccan energy system description and criticism of its performance and ability to cope with the government international engagements concerning greenhouse gases emissions and also national engagements mostly the need to overcome the demand-supply related issues. Keywords: Energy modeling, Multi-agents models, Moroccan energy system JEL Classifications: C53, Q42, Q56 DOI: https://doi.org/10.32479/ijeep.8505